The Documents of Algerian Liberation Revolution and The Problematic of State Building - Daas Amieur, Salah (Journal of Human Sciences, 2021)
The charters of the Algerian liberation revolution raise many problems and questions that have not been discussed yet, but many of them are still subject to political disagreements, disagreements and employment. Perhaps the most important thing is whether these pacts carry any model or approach to the Algerian state to be built after independence. To answer this question, we had to address the basic charters of the editorial revolution, the statement of November 1, the Somam’s document and the Tripoli Conference document. These charters, which date decisive stages and detailed turns in the course of the revolution, reflect in their entirety the internal conflicts between the revolution leaders over political and ideological choices on the one hand, and the legitimacy of those who rule in independant Algeria on the other hand.